Synthesis of highly functionalized β-aminocyclopentanecarboxylate stereoisomers by reductive ring opening reaction of isoxazolines - Nonn, Melinda; Kiss, Loránd; Sillanpää, Reijo; Fülöp, Ferenc (Beilstein Journal of Organic Chemistry, 2012)
A rapid and simple procedure was devised for the synthesis of multifunctionalized cyclic β-amino esters and γ-amino alcohols via the 1,3-dipolar cycloaddition of nitrile oxides to β-aminocyclopentenecarboxylates. The opening of the isoxazoline reductive ring to the corresponding highly functionalized 2-aminocyclopentanecarboxylates occurred stereoselectively with good yields.
Keywords: amino acids; cycloaddition; functionalization; isoxazolines; reduction